THE SOUTH-EASTERN BORDER REGION OF THE HITTITE STATE - Ghazaryan Robert (Bulletin of the institute of oriental studies (Online), 2016)
Tegarama was one of the eastern lands of the Hittite Kingdom. In the geographic sense it is part of the Armenian Highland that is why its history is of special interest to us. Taking into account the fact that the Armenian people had considerable ethnic ties with the Upper Euphrates region, specialists have traditionally tended to identify “Home of Torgom” in the Trans Euphrates region together with the city Tegarama (Assyrian Til-Garimmu) mentioned from the 2nd millennium BC. “Home of Torgom” literally repeats Bet-Togarma mentioned in the Bible. The study of the history of the country of Tegarama is also important because in Armenian historiography, starting from Movses Khorenatsi, Armenian ancestor Hayk is called “Son of Torgom”, and the Armenian people - “People of Torgom”. Most of the researchers located Tegarama in the place of the present settlement Gyurun. By comparing the “Cappadocian”, Hittite and Assyrian sources, Tegarama can be located in the Upper Euphrates valley, on the right bank of the river, to the north of Kargamis, to the west of Isuwa, to the south of Upper Land and to the east of Kanes. The territory of Tegarama was not far from Nesa - one of the initial centers of the Hittites; and it was also one of the initial places of inhabitance of the Hittites. Tegarama also occupied a strategically important position. On the one hand it bordered on the country of Mitanni, on the other hand - on Isuwa. Thus, the country of Tegarama occupied a significant geographic position: on the one hand roads led from here to other western districts of the Armenian Highland, to Tsopk, and on the other hand - to Northern Syria and Northern Mesopotamia. It was also one of the spiritual centers of Hatti.